2017
DOI: 10.1021/jacs.7b05732
|View full text |Cite
|
Sign up to set email alerts
|

Control of Rectification in Molecular Junctions: Contact Effects and Molecular Signature

Abstract: Thin layers of oligomers with thickness between 7 and 9 nm were deposited on flat gold electrode surfaces by electrochemical reduction of diazonium reagents, then a Ti(2 nm)/Au top contact was applied to complete a solid-state molecular junction. The molecular layers investigated included donor molecules with relatively high energy HOMO, molecules with high HOMO-LUMO gaps and acceptor molecules with low energy LUMO and terminal alkyl chain. Using an oligo(bisthienylbenzene) based layer, a molecule whose HOMO e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 96 publications
2
90
1
Order By: Relevance
“…Recently, various groups succeeded in fabricating molecular devices exhibiting rectification ratios (RRs) larger than 10 2 or even 10 5 . 12 15 , 23 , 24 , 63 68 In view of such achievements, it is hard to discuss “rectification” based on the very modest values RR ≈ 1.5 that characterize CnT junctions. However – and this is the important point we want to make here – these small RR-values are merely a consequence of the fact that the HOMO of CnT does not respond to the entire substrate-tip bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, various groups succeeded in fabricating molecular devices exhibiting rectification ratios (RRs) larger than 10 2 or even 10 5 . 12 15 , 23 , 24 , 63 68 In view of such achievements, it is hard to discuss “rectification” based on the very modest values RR ≈ 1.5 that characterize CnT junctions. However – and this is the important point we want to make here – these small RR-values are merely a consequence of the fact that the HOMO of CnT does not respond to the entire substrate-tip bias.…”
Section: Resultsmentioning
confidence: 99%
“…To become part of nanotechnology, molecular electronics should be able to fabricate molecular devices that supersede or at least undertake the basic functions of circuit components employed nowadays in semiconductor-based microelectronics. 1 15 Rectification represents such an outstanding function, which has attracted the attention of the community since its inception. 16 In molecular junctions where charge transport is dominated by a single molecular orbital (MO) one may intuitively expect that rectification is directly related to the bias-driven shift of the MO energy 17 20 in principle determined by the local electric potential φ , which varies linearly across the junction (“potentiometer rule”) in the absence of screening.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to prepare graphene ribbons from diazonium salts. Molecular junctions using aryl oligomers were obtained from diazonium salts [38]. An organic oligomeric aryl layer was grown on a conducting substrate and capped with, for example, a gold layer; this provided a molecular junction between two conducting materials [39].…”
Section: The Different Surfaces That Can Be Graftedmentioning
confidence: 99%
“…Many studies has been reported quite recently using diazonium electroreduction to graft conductive oligomers on surfaces [38,[43][44][45][46][47]. Ultrathin layers can be generated since the growth is limited by the conductivity of the organic layer in the potential range required for the electroreduction of the diazonium salt.…”
Section: Introductionmentioning
confidence: 99%